Effect of hydrothermal duration on the properties of iron-cobalt-selenide (FECO2SE4) as counter electrode for dye-sensitized solar cells / Puteri Najihah Megat Zakaria - Megat Zakaria, Puteri Najihah (2024)
This work reports on the synthesis of iron selenide (FeSe2), cobalt selenide (Co3Se4) and iron cobalt selenide (FeCo2Se4) via a two-step hydrothermal process. The formation of FeSe2, Co3Se4 and FeCo2Se4 have been proven by sample characterization to support their catalytic activity as the counter electrodes for solid-state dye-sensitized solar cells (DSSCs).